Initial Validation of a Chinese Version of the Mental Health Literacy Scale Among Chinese Teachers in Henan Province - Chen, Shen (Front Psychiatry, 2021)
Background: Teachers' Mental health literacy (MHL) is one of the important factors that influence students' mental health literacy and even their mental health status. A valid, comprehensive measure is needed to adequately identify MHL levels in the Chinese teachers. Thus, this study aimed to validate a Chinese version of the Mental Health Literacy Scale (MHLS) among Chinese teachers. Methods: A total of 367 Chinese primary and secondary school teachers in Henan province were enrolled to complete the Chinese version of MHLS and several validation measures. Results: A parallel analysis supported a four-factor structure model of the Chinese version, but because of the low communalities and mean factor loadings, the univariate structure of the original scale was selected. Additionally, the criterion construct validity of the Chinese version was supported by significant correlations with self-efficacy in coping with mental health problems, mental health status, the stigma associated with receiving mental health treatment, and socially distancing from patients with mental illness. The Cronbach's α of the Chinese version was acceptable. Females, younger teachers, teachers with higher educational level, and full-time mental health teachers showed higher levels of MHL. Conclusion: The Chinese version of MHLS is a valid and reliable tool to assess the level of Chinese teachers' MHL.